2017
DOI: 10.1016/j.acap.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Receipt of Pressure Equalization Tubes Among US Children, 2014

Abstract: Objectives Pressure equalization tube (PET) placement (also referred to as tympanostomy tube placement) is among the most common ambulatory surgical procedures performed on U.S. children. Over twenty years ago, differences by race/ethnicity in the national prevalence of having had PETs placed were documented. Whether these differences persist is unknown. Methods We used data from the 2014 National Health Interview Survey to examine the percentage of children 0-17 years of age that have ever undergone PET pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 22 publications
0
40
2
Order By: Relevance
“…It is worth re‐emphasizing here that only studies in which the actual delivery or outcome of care varied between racial/ethnic groups were included in this analysis. These racial/ethnic disparities were often independent of SES . They are also closely related to eroded physician trust because racial/ethnic minorities have historically experienced higher levels of distrust in healthcare providers .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is worth re‐emphasizing here that only studies in which the actual delivery or outcome of care varied between racial/ethnic groups were included in this analysis. These racial/ethnic disparities were often independent of SES . They are also closely related to eroded physician trust because racial/ethnic minorities have historically experienced higher levels of distrust in healthcare providers .…”
Section: Discussionmentioning
confidence: 99%
“…Targeting such societal factors contributing to disparate SES is not the subject of this article or purview of pediatric otolaryngology per se. However, a better understanding of the sequelae of low SES within our field can at least increase awareness of at-risk patients and possibly promote personal or institutional-level adjustments [34][35][36][37] Medicaid patients delayed referral for RAOM 24 Lower SES with higher risk OM 7,23,35,[38][39][40] Black/Hispanic patients less likely to afford medications or see specialist for FEI 25,26 FEI more common in whites, lower SES 41 Hearing loss/rehabilitation Rural patients less aware of NBHS results and have poorer failed NBHS follow-up 12,21,42 Rural PCPs less confident in NBHS follow-up 22 Public/no insurance delayed to CI 43,44 Lower CI rates in blacks/Hispanics, lower SES 45,46 Medicaid worse CI follow-up, more complications 47 HL, delay to aids associated with lower SES [48][49][50][51][52][53] SDB/tonsillar pathology SDB/OSA Delay to PSG and surgery in lower SES 18,27 Racial minorities, lower SES higher risk SDB 14,54,55 Adenotonsillectomy Racial minorities, lower SES more complications 29,56 Medicaid less likely to get AT referral 37,57 Blacks with higher risk persistent postoperative OSA 28…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a recent analysis of tympanostomy tube utilization in the U.S. showed that white children receive tubes far more commonly than black or Hispanic children, however indication for surgery was not ascertained 42 . It is possible that this difference in utilization could be associated with increased rates of tubes placed for RAOM in white children.…”
Section: 4 Discussionmentioning
confidence: 99%